Perancangan Enterprise Architecture Menggunakan TOGAF Architecture Development Method (Studi Kasus: Objek Wisata Janti Park) - Shafira Nur Herlinda; Teguh Susyanto; Budi Hartanto (Jurnal Data Mining dan Sistem Informasi, 2023)
Janti Park Tourism Object in utilizing information systems and information technology to support business processes is still not optimal. Utilization of information systems is currently only carried out in the business process of selling parking tickets and entrance tickets. However, other business processes are still carried out manually and not yet computerized. This causes a high risk of human error, successive recording errors, data that is easily lost and damaged, resulting in inaccurate data. The purpose of this study was to produce an enterprise architecture design using the TOGAF Architecture Development Method in the form of an application blueprint that is used as a reference in developing information systems and information technology so that they can be more optimal and increase the effectiveness and efficiency of business processes at Janti Park Tourism Object. The design of enterprise architecture uses the TOGAF Architecture Development Method (ADM) with 8 development phases, namely the preliminary phase, requirements management, architecture vision, business architecture, information systems architecture, technology architecture, opportunities and solutions, and migration planning. This research produces an application blueprint that can be used as a guide and reference in developing information systems and information technology so that they can be more optimal and increase the effectiveness and efficiency of the Janti Park Tourism Object business process.